Mango Pudding (Mangifera indica fruit pudding) sebagai Alternatif Pereda Nyeri pada Dismenore Remaja - Ulimafissudur, Asri Syifa; Abdurrahman, Fauzah Lathifah (JGK: Jurnal Gizi dan Kesehatan, 2024)
Background : Dysmenorrhea, menstrual pain, often affects the well-being of adolescent girls. Objective : This research aims to determine the quality of mango fruit pudding and as an alternative pain reliever for dysmenorrhea. Method : wiith an experimental design, the research was carried out at the MA Miftahunnajah Sleman Yogyakarta Science Laboratory for three months. Mango fruit was chosen because it contains vitamin C and antioxidant compounds which can relieve symptoms of dysmenorrhea. The process of making pudding involves peeling, slicing and mashing mangoes, which are then mixed with gelatin, water and sugar. Results : pudding shows an attractive appearance and a simple manufacturing process. Involving 40 female teenagers, the research combined observation and questionnaire methods. Likert scale analysis shows an average satisfaction level of 77.52%, with positive assessments especially on taste, texture, packaging and product quality. In Conclusion : mango fruit pudding can be considered an effective and attractive option in treating dysmenorrhea in adolescent girls, providing potential additional benefits from the nutritional content of mango fruit. This product can be used as a satisfactory alternative to relieve menstrual pain in adolescent women.